2021
DOI: 10.1101/2021.10.24.465621
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Density-dependent selection in Drosophila: evolution of egg size and hatching time

Abstract: Many different laboratory studies of adaptation to larval crowding in Drosophila spp. have all yielded the evolution of pre-adult competitive ability, even though the ecological context in which crowding was experienced varied across studies. However, the evolution of competitive ability was achieved through different suites of traits in studies wherein crowding was imposed in slightly different ways. Earlier studies showed the evolution of increased competitive ability via increased larval feeding rate and to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Consequently, the larval density conditions in the present assays are different from previous assays of life-history traits in these populations under low and high larval densities (e.g. Sarangi et al 2016; Sarangi 2018; Venkitachalam et al 2022).…”
Section: Methodsmentioning
confidence: 73%
See 1 more Smart Citation
“…Consequently, the larval density conditions in the present assays are different from previous assays of life-history traits in these populations under low and high larval densities (e.g. Sarangi et al 2016; Sarangi 2018; Venkitachalam et al 2022).…”
Section: Methodsmentioning
confidence: 73%
“…Consequently, another set of D. melanogaster populations (LCU populations: see Materials and Methods), derived from the same ancestral controls as the MCU populations, and adapted to larval crowding at an egg number and food level combination similar to that of the D. melanogaster populations of Mueller et al (2000), was found to have evolved to adapt to chronic larval crowding via traits such as increased larval feeding rate, similar to those evolved by the populations used by Mueller et al (2000) (Sarangi 2018). As a result of these various studies, it became clear that the LCU and MCU populations, which shared ancestral controls, evolved to adapt to chronic larval crowding via different suites of traits as a result of the different combinations of egg number and food level at which they experienced crowding (Sarangi 2018; Venkitachalam et al 2022). These studies, thus, paved the way for testing the speculative predictions made by Dey et al (2012) about whether the specific traits that evolve in response to chronic larval crowding could affect whether or not population stability evolves as a correlated response to density-dependent selection.…”
Section: Introductionmentioning
confidence: 99%